Formal rural credit for rural development in bantul district, special province of Yogyakarta : provision, use and needs - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1990)
After outlining the shift in interpretation of the concept and objectives of rural development since the mid-1960s, the main consequences of the new role assigned to formal credit in the desired rural transformation process are explored. Againts this background, some general characteristics of rural credit provision in Indonesia are summarized. Subsequently, the study deals with the present-day role of formal rural credit in the process of rural development in a densely populated, but internally heterogeneous district south of Yogyakarta city. The credit supply system in the area, the actual use of credit by . the house holds in the various agro-physical zones, and the appraised needs for credit in these subdivisions are presented The test con dudes with recommendations for a policy of rural credit provision which is better attuned to_ the socio-economic circumstances as present in the geographical setting of this part of central Java, Indonesia.